PedsCases - A Learning Module for Evaluation of Acute Otitis Media in Children: Medical Students - Peter Gill; Michael Kapusta; Peter MacPherson; Sarah Forgie (MedEdPORTAL, 2010)
Abstract This podcast-based learning module reviews an approach to the evaluation of acute otitis media in children. It is intended for medical students and reviews the common and more serious causes of acute otitis media. Subsequently, a case presents a previously well child who presents with acute ear pain. The case evaluates the proper evaluation and workup of acute otitis media. This resource is a part of PedsCases, a comprehensive web-based educational tool that focuses on the core objectives of undergraduate pediatric education with extensive student involvement. PedsCases was created for and by medical students and provides an opportunity for active self-directed learning in pediatrics. The learning modalities available include questions, flash card–type quizzes, multistep clinical cases, and podcasts.